“I hate public transport and I go by car that I bought on installment” humor and social criticism in Max Gonzaga’s “Middle Class” (Orfeu, 2023)
This article presents the results of a research that took as its object the song “Classe Medio”, by Max Gonzaga. Composed and released in 2005, the song not only had repercussions at the time of its release, but also in later periods, which generated interest in studying it more closely. For this, we carried out an documental analysis of its recording having as main reference the semiotics of the song to reveal the relations that are established between lyrics and music for the production of its meanings. The analyzes show that the song builds, through the key of humor, a critique of the alignment of intermediate sectors of Brazilian society to the ideology of the elites, revealing the importance of melody, harmony and interpretative choices for the establishment of its ironic and cartoon.
Keywords: Max Gonzaga; Middle class; Popular song and criticism